Computer simulation model of single stage direct control of DC machines fed AC voltage source using single-phase matrix converter (SPMC) / Nur Hidayah Abdullah … [et al.] - Abdullah, Nur Hidayah; Baharom, Rahimi; Mohamad Rawi, Muhammad Shawwal; Mohd Ghazali, Mohd Shukri (Universiti Teknologi MARA, 2021)
This paper aims to present a new model of the single-stage direct control of DC machines fed with an AC voltage source using a Single-Phase Matrix Converter (SPMC). The proposed system uses a single circuit topology to perform four-quadrant control operations. Besides, enabling four quadrants control operation, the proposed circuit topology can be controlled to provide almost unity power factor operation using the supply current wave shaping technique. It features low power losses resulting in high power density. The theoretical model of the switching algorithms of the SPMC is utilized to control the desired output according to the characteristics of quadrant I, II, III, and IV operations. The simulation model of the proposed converter is developed using MATLAB/Simulink to investigate the circuit behaviors. The selected results are presented to verify the proposed converter.